(untitled) (Asian Journal of Ethnobiology, 2021)
Abstract. Afrianto WF, Tamnge F, Hidayatullah T, Hasanah LN. 2021. Local knowledge of plant-based nutrition sources from forgotten foods in Datengan Village, East Java, Indonesia. Asian J Ethnobiol 4: 53-64. Plant-based food has benefits for health and the environment. Finding adequate plant-based nutrition sources can be found by exploring local knowledge. Here, forgotten foods mean two definitions that (i) those foods were consumed by the community before, but over time it is forgotten in the daily diet, and (ii) unusually consumed by the community outside, but it still is or over-consumed by the community. This study aimed to identify the plant-based nutrition sources in Datengan Village. The study was conducted in the Datengan Village, Grogol Sub-district, Kediri District, East Java Province, Indonesia. Ethnobotany approach through qualitative research (i.e., observation, semi-structured interview, and participant observation) were used to explore the plant-based nutrient sources from forgotten foods in Datengan Village. The results showed forgotten foods in Datengan Village, i.e., fermented foods, mushrooms, by-products, and plant rich-nutrition. There were 26 plant-rich-nutrition, two mushrooms, two fermented foods, and six by-product foods. This investigation is still a preliminary study. 14 handling, processing, and serving methods were used based on the interview. This plant-based nutrition source diversity can be an alternative to fulfill nutrient requirements for the community of Datengan Village and the community of outside areas.